ANALYSIS OF MATERNAL AGE AT MARRIED, NUMBER OF CHILDREN, HISTORY OF BREASTFEEDING, MOTHER'S EDUCATION AND HIGH RISK OF PREGNANCY WITH INCIDENCE OF STUNTING IN CHILDREN UNDER FIVE-YEARS - Eka Sri Purwandari; Qorinah Estiningtyas Sakilah Adnani; Reni Yuli Astutik (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2021)
Background: Stunting among children is a problem that has received serious attention from the Indonesian government. Incidence of stunting has decreased from year to year, but the decline still does not meet the World Health Organization (WHO) target. Stunting occurs as a result of chronic malnutrition, especially during the first 1000 days of birth as a vital phase. Chronic nutritional deficiency as a toddler can be caused by various factors, including exclusive breastfeeding, the number of children that must be borne by the family and mother's education. Purpose: This study aimed to analyse the age of the women at marriage, the number of children, mother’s education, history of breastfeeding and pregnancy risk with the incidence of stunting in children under five years.. Methods: The design of this study was analytic with a cross-sectional approach. This research was conducted on toddlers aged 13-60 months in a village of East Java Province, Indonesia, with a sample size of 110 children under five. The statistical test used logistic regression with a confidence level of 95%. Results: Data analysis using logistic regression reveal the relationship between the dependent variable and the incidence of toddler stunting, the following results were obtained: from the mother's age at marriage, the value of ? 0.286, the number of family members ? 0.587, mother's education, ? 0.002, history of breastfeeding, ? 0.884, risk of pregnancy ? 0.696. of the five factors associated with the incidence of under-five stunting in this study, it shows that only mother's education has a very significant relationship with the incidence of under-five stunting (? = 0.002 <? = 0.05). The OR value is 4.724, which means that mothers with primary education have a risk of 4.724 times in the incidence of child stunting. Conclusion: The lower the mother's education provides an opportunity for the incidence of toddler stunting. Maternal education is related to the ability to receive information related to nutrition and child development so that it also has an impact on the preparation of family nutrition. In the long term, improper nutrition can lead to stunting.